Bismuth nitrate as a source of nitro radical in ipso-nitration of carboxylic acids. (1st November 2019) - Agasti, Soumitra; Maiti, Siddhartha; Maity, Soham; Anniyappan, M.; Talawar, M.B.; Maiti, Debabrata
Graphical abstract: Aromatic nitro compounds are extensively used in synthetic chemistry. We disclose a new approach to obtain nitroarenes regioselectively starting from carboxylic acids under acid-free reaction conditions. Abstract: Aromatic nitro compounds are extensively used in synthetic chemistry. We disclose a new approach to obtain nitroarenes regioselectively starting from carboxylic acids under acid-free reaction conditions.